Non-covalent functionalization of WS2 monolayer with small fullerenes: tuning electronic properties and photoactivity. Issue 34 (2nd August 2016) - Luo, Cai-Yun; Huang, Wei-Qing; Hu, Wangyu; Peng, P.; Huang, Gui-Fang
Abstract : Atomically thin 2-D transition metal dichalcogenide (TMDCs) heterostructures have attracted growing interest due to their massive potential in solar energy applications due to their visible band gap and very strong light–matter interactions. Abstract : Atomically thin two-dimensional transition metal dichalcogenides (TMDCs) heterostructures have recently attracted growing interest due to their massive potential in solar energy applications due to their band gap in the visible spectral range and extremely strong light–matter interactions. Herein, heterostructures composed of WS2 and MoS2 monolayers, as representative TMDCs, with small fullerenes (B12 and C20 ) are investigated to explore their applications in solar energy conversion using first principles calculations based on density functional theory (DFT). The WS2 (MoS2 ) monolayer and fullerene form a van der Waals (vdW) heterostructure. Compared to pure monolayers, the heterostructures have a smaller band gap, which favours enhancing visible light absorption. The amount of charge transfer at the interface induced by vdW interactions depends on the type of fullerene. Most importantly, a type-II staggered band alignment is formed between WS2 (MoS2 ) and fullerene with the latter possessing the higher electron affinity which results in the robust separation of photoexcited charge carriers between them. These results indicate that the electronic properties and photoactivity of TMDCs monolayers can be tuned by non-covalent coupling with small fullerenes, thus meeting the needs of various applications.